Frecuencia relativa de Boophilus microplus (Acari: Ixodidae) en bovinos (os taurus y B. indicus) en ocho zonas ecológicas de Costa Rica - Alvarez, V (2003)
The research on the relative abundancy of Boophilus microplus took place in ten farms, distributed in eight ecological zones (EZ) and two rainfall systems of Costa Rica. Monthly visits were made to pick up ticks larger than 4mm from the right side of the animals. The total number of ticks was increased by two and divided between the total of sampled bovines per farm. Farm visits were adjusted to animals bath to allow the recovery of the tick population. B. microplus was detected in all sampled farms throughout the year. Media comparison statistic analyses were made and no differences were found among EZ, farms and seasons. On the contrary, there were important statistical differences between rainfall systems. The rainfall system 1, that included rain seasonality, showed larger tick infestations (p = 0.03). An isothermal and low variability regarding relative humidity situations were present in some of the areas included in this research. Bath intensity was lower to other past studies. Eventhough no differences were found between production systems, it is important to emphasize that bath intensity was higher in european cattle farms, in comparison to others of the same EZ, but of crossbred. A tick manual removable system was recommended in dual-purpose and specialized dairy farms with no more than 30-35 animals, as an alternative feasible system that significantly reduced acaricide use.